2022
DOI: 10.1021/acsanm.1c03577
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Cationic Organic Cages for Trapping Heavy Metal Oxyanions

Abstract: The harmful effect of poisonous oxoanions on the water environment highlights the urgent demand for effective adsorption materials. Rather than utilizing open framework materials carrying continuous pores as oxoanion traps, nanoporous molecular cages with discrete pores show promise since they are supposed to have higher adsorption efficiency. However, they are rarely reported in the field of decontamination. Herein, we utilize a nanoporous cationic organic cage, I-Cage-Cl, as a type of adsorbent that can effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The supernatant was then measured using a UV–vis spectrophotometer to determine the concentration of the residual RhB molecule in the solution. The adsorption capacity ( q ) and removal percentage ( R ) of the RhB molecule were calculated by eqs – q t = ( C 0 C t ) × V m q e = false( C 0 C e false) × V m R = false( C 0 C t false) C 0 × 100 % …”
Section: Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was then measured using a UV–vis spectrophotometer to determine the concentration of the residual RhB molecule in the solution. The adsorption capacity ( q ) and removal percentage ( R ) of the RhB molecule were calculated by eqs – q t = ( C 0 C t ) × V m q e = false( C 0 C e false) × V m R = false( C 0 C t false) C 0 × 100 % …”
Section: Experimental Proceduresmentioning
confidence: 99%
“…The Langmuir adsorption model was used to explain the adsorption behavior and related to the adsorption capacity of RhB as a function of equilibrium concentration at room temperature. The linear form of the Langmuir isotherm equation is expressed in eq , where k b (L mg –1 ) is the Langmuir adsorption constant concerned with the binding sites C e q e = 1 q m k b + C e q m …”
Section: Experimental Proceduresmentioning
confidence: 99%
“…Zhao and co-workers synthesized a highly charged POC: I-Cage-Cl, which could efficiently select and trap CrO 4 2À ions in water owing to the strong affinity between the electropositive I-Cage-Cl and the CrO 4 2À anion. 123 Recently, some studies revealed the possible application of POCs for trapping the pollutants in sewage. Yang et al 122 used N,N-dimethylformamide (DMF) as a solvent and introduced different dihydrazide linkers onto the concave-shaped tetraformyl-functionalized C4RACHO scaffold, and the seven obtained types of calix [4]-resorcinarene-based POCs (HPOC-101, 102, 103, 104, 201, 301, and 401) all exhibited an I 3 À adsorption capability in water.…”
Section: Water Desalination and Sewage Purificationmentioning
confidence: 99%
“…Zhao and co-workers synthesized a highly charged POC: I-Cage-Cl, which could efficiently select and trap CrO 4 2− ions in water owing to the strong affinity between the electro-positive I-Cage-Cl and the CrO 4 2− anion. 123…”
Section: Othersmentioning
confidence: 99%